2003
DOI: 10.3732/ajb.90.12.1736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inbreeding on male function and self‐fertility in the partially self‐incompatible herb Campanula rapunculoides (Campanulaceae)

Abstract: We examined the effect of inbreeding on fitness (through both male and female functions) and changes in self-fertility in the partially self-incompatible species Campanula rapunculoides. Individuals in natural populations of C. rapunculoides varied extensively in their strength of self-incompatibility (SI). We crossed 11 individuals that differed in their strength of SI to generate families with four levels of inbreeding (f = 0.0, 0.25, 0.5, and 0.75). Progeny were scored for three traits related to male fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…For example, Waser et al studied seed yield in populations of Ipomopsis aggregata , a predominately outcrossing plant with late-acting self-incompatibility, and showed that maternal variance in seed yield ranges between 12 and 35 % (Waser et al 1995 ). Similarly, Good-Avila and Stephenson show that in the partially self-incompatible C. rapunculoides , maternal variation accounts for 36 % of the phenotypic variance in seed yield (Good-Avila et al 2003 ). Lipow and Wyatt show that maternal effect accounts for between 20.5 and 37.1 % of the phenotypic variance in seed yield in the largely outcrossing A. incarnate (Lipow and Wyatt 1999 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Waser et al studied seed yield in populations of Ipomopsis aggregata , a predominately outcrossing plant with late-acting self-incompatibility, and showed that maternal variance in seed yield ranges between 12 and 35 % (Waser et al 1995 ). Similarly, Good-Avila and Stephenson show that in the partially self-incompatible C. rapunculoides , maternal variation accounts for 36 % of the phenotypic variance in seed yield (Good-Avila et al 2003 ). Lipow and Wyatt show that maternal effect accounts for between 20.5 and 37.1 % of the phenotypic variance in seed yield in the largely outcrossing A. incarnate (Lipow and Wyatt 1999 ).…”
Section: Discussionmentioning
confidence: 95%
“…Maternal roles in differential reproductive success have also been demonstrated using different experimental strategies. For example, diallel analysis verifies significant maternal variation in seed yield in Ipomopsis aggregate, Companula rapunculoides, Asclepias incarnate and Leavenworthia crassa (Waser et al 1995 ; Lyons 1996 ; Lipow and Wyatt 1999 ; Good-Avila et al 2003 ). More direct manipulations that alter the conditions of maternal tissues, such as water, nutrients or age, verify the role of maternal tissues in differential mating [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Inbreeding depression for cumulative fitness was very high, with inbred individuals having on average only 6% of the fitness of outcross plants in three separate annual cohorts. This number may even be an overestimate, as male fitness was not measured and often declines with inbreeding (Carr & Dudash, 1997; Good‐Avila et al ., 2003; Hayes et al ., 2005a). Inbreeding depression is the result of the expression of recessive deleterious alleles following inbreeding (reviewed in Charlesworth & Charlesworth, 1999; Carr & Dudash, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…If pollen from outcrossing species has evolved to compete in matings where there is parental conflict, the pollen may have evolved competitive traits that pollen from inbreeding species have not. For example, a study examining the effects of male fertility in Campanula rapunculoides, a species with individuals ranging from SC to strongly SI, Good-Avila et al (2003), found that inbreeding negatively affected pollen performance. In N. plumbaginifolia, we found a significant heterospecific effect on SS in general and in some crosses.…”
Section: Nicotiana Plumbaginifolia Prefers Heterospecific Pollenmentioning
confidence: 98%